2016
DOI: 10.1002/ece3.2157
|View full text |Cite
|
Sign up to set email alerts
|

Adaptional evolution of trichome in Caragana korshinskii to natural drought stress on the Loess Plateau, China

Abstract: Caragana korshinskii is commonly employed to improve drought ecosystems on the Loess Plateau, although the molecular mechanism at work is poorly understood, particularly in terms of the plant's ability to tolerate drought stress. Water is the most severe limiting factor for plant growth on the Loess Plateau. The trichome is known to play an efficient role in reducing water loss through decreasing the rate of transpiration, so in this study, we focused on the trichome‐related gene expression of ecological adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 53 publications
(85 reference statements)
2
32
0
2
Order By: Relevance
“…The annual precipitation, annual evaporation, soil moisture content (SMC) and plant leaf water potential were reported previously [25]. However, no significant difference was detected in the annual average temperature from the northwest to the southeast, soil pH and altitude along the precipitation gradient [26]. The collection and freezing of plant materials and soil samples with respect to C. korshinskii were described previously [27].…”
Section: Sampling Sites Conditions and Plant Materialsmentioning
confidence: 99%
“…The annual precipitation, annual evaporation, soil moisture content (SMC) and plant leaf water potential were reported previously [25]. However, no significant difference was detected in the annual average temperature from the northwest to the southeast, soil pH and altitude along the precipitation gradient [26]. The collection and freezing of plant materials and soil samples with respect to C. korshinskii were described previously [27].…”
Section: Sampling Sites Conditions and Plant Materialsmentioning
confidence: 99%
“…Trichomes affect the optical properties of the leaf surface and may protect plants from stress damage and reduced water loss through decreasing the rate of transpiration [34][35][36]. In the current study, we revealed that the density and number of epidermal trichomes on the abaxial side of leaves were higher in the transgenic plants than in the WT plants.…”
Section: Transgenic Plants Heterologously Expressing Rty Have Increasmentioning
confidence: 44%
“…The trichome is an important diagnostic character used in plant identification and plant taxonomy, and is involved in deterring herbivore attack and in adaptation to adverse environments [3,4,54]. Unlike A. thaliana , poplar trichomes never undergo branching.…”
Section: Resultsmentioning
confidence: 99%